2013
DOI: 10.1111/aej.12039
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ethylenediaminetetraacetic acid by a 940 nm diode laser for enhanced removal of smear layer

Abstract: Laser enhancement of ethylenediaminetetraacetic acid with cetrimide (EDTAC) has previously been shown to increase removal of smear layer, for middle-infrared erbium lasers. This study evaluated the efficiency of EDTAC activation using a near-infrared-pulsed 940 nm laser delivered by plain fibre tips into 15% EDTAC or 3% hydrogen peroxide. Root canals in 4 groups of 10 single roots were prepared using rotary files, with controls for the presence and absence of smear layer. After laser treatment (80 mJ pulse(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Recently, Lagemann et al (2014) have shown that, when using the 940nm laser diode associated only with EDTA, the SL elimination is significantly superior compared with the conventional irrigation syringe technique. The risk of apical penetration by the irrigation solution is greatly reduced when using the laser diode which produces fluid movement by 4-5mm/s, compared to the erbium laser which causes a speed of about 30 mm/s [6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lagemann et al (2014) have shown that, when using the 940nm laser diode associated only with EDTA, the SL elimination is significantly superior compared with the conventional irrigation syringe technique. The risk of apical penetration by the irrigation solution is greatly reduced when using the laser diode which produces fluid movement by 4-5mm/s, compared to the erbium laser which causes a speed of about 30 mm/s [6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…Jain 2012 used a similar in vitro fluorescent technique to measure the percentage of bacteria kill on matured biofilm, warm CHX reported an average 67% dead bacteria compared cold CHX at only 20% [20]. While a rise in temperature could damage the surrounding periodontal tissues, Schoop et al [30] however reported that diode lasers had the safest temperature increase compared to other lasers, hence is ideal for root canal disinfection [31]. Regardless of the design of the end firing tip (radial or forward firing) it is important to ensure that the dose is adjusted based on the volume of the canal and tip is in constant motion while activated in the root canal [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Intracanal diode laser application is used for removal of smear layer (Saghiri et al, 2012;Lagemann et al, 2014;Sohrabi et al, 2016), root canal disinfection (Mehrvarzfar et al, 2011;Beer et al, 2012;Bago et al, 2013;Neelakantan et al, 2015;Sohrabi et al, 2016) and increase in bond strength of sealers (Moura-Netto et al, 2012;Das et al, 2013;Maenosono et al, 2015). However, according to our literature search, there are not many in vivo studies about intracanal diode laser application (Morsy et al, 2018;Genc Sen and Kaya, 2019) and there is no study relating to the association between pain during intracanal diode laser application factors such as demographic, preoperative and postoperative factors.…”
Section: Discussionmentioning
confidence: 99%